2020
DOI: 10.3389/fnhum.2020.00303
|View full text |Cite
|
Sign up to set email alerts
|

Children With Developmental Coordination Disorder Exhibit Greater Stepping Error Despite Similar Gaze Patterns and State Anxiety Levels to Their Typically Developing Peers

Abstract: This study examined stepping accuracy, gaze behavior, and state-anxiety in children with (N = 21, age M = 10.81, SD = 1.89) and without (N = 18, age M = 11.39, SD = 2.06) developmental coordination disorder (DCD) during an adaptive locomotion task. Participants walked at a self-selected pace along a pathway, placing their foot into a raised rectangular floor-based target box followed by either no obstacles, one obstacle, or two obstacles. Stepping kinematics and accuracy were determined using three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
2
11
0
Order By: Relevance
“…Evidently, anxiety is a critical factor that must be considered to fully understand the mechanisms underpinning the visuomotor control strategies of children with DCD during stair negotiation. Though we have recently shown that children with DCD do not experience heightened anxiety during over ground targeted stepping tasks (Parr et al, 2020), stair negotiation is likely to place greater demands on dynamic stability and increase the risk of significant injury in the event of a fall and may, therefore, be more likely to instill a fear response.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Evidently, anxiety is a critical factor that must be considered to fully understand the mechanisms underpinning the visuomotor control strategies of children with DCD during stair negotiation. Though we have recently shown that children with DCD do not experience heightened anxiety during over ground targeted stepping tasks (Parr et al, 2020), stair negotiation is likely to place greater demands on dynamic stability and increase the risk of significant injury in the event of a fall and may, therefore, be more likely to instill a fear response.…”
Section: Introductionmentioning
confidence: 89%
“…Consequently, children with DCD may formulate inaccurate stepping actions due to the suboptimal use of gaze to extract relevant and timely information from the environment, and the inability to predict the consequences of the ensuing movement (Wilson et al, 2013). Though our recent findings suggest that stepping inaccuracies in children with DCD may also occur despite typical looking behavior (Parr et al, 2020), it is important to determine whether the visuomotor control strategies adopted by children with DCD may be contributing to difficulties with stair negotiation.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations